Adaptive evolution and metabolic engineering of a cellobiose- and xylose- negative Corynebacterium glutamicum that co-utilizes cellobiose and xylose. Issue 1 (December 2016) - Lee, Jungseok; Saddler, Jack; Um, Youngsoon; Woo, Han
Abstract Background An efficient microbial cell factory requires a microorganism that can utilize a broad range of substrates to economically produce value-added chemicals and fuels. The industrially important bacteriumCorynebacterium glutamicum has been studied to broaden substrate utilizations for lignocellulose-derived sugars. However, C. glutamicum ATCC 13032 is incapable of PTS-dependent utilization of cellobiose because it has missing genes annotated to β-glucosidases (bG) and cellobiose-specific PTS permease. Results We have engineered and evolved a cellobiose-negative and xylose-negativeC. glutamicum that utilizes cellobiose as sole carbon and co-ferments cellobiose and xylose. NGS-genomic and DNA microarray-transcriptomic analysis revealed the multiple genetic mutations for the evolved cellobiose-utilizing strains. As a result, a consortium of mutated transporters and metabolic and auxiliary proteins was responsible for the efficient cellobiose uptake. Evolved and engineered strains expressing an intracellular bG showed a better rate of growth rate on cellobiose as sole carbon source than did other bG-secreting or bG-displayingC. glutamicum strains under aerobic culture. Our strain was also capable of co-fermenting cellobiose and xylose without a biphasic growth, although additional pentose transporter expression did not enhance the xylose uptake rate. We subsequently assessed the strains for simultaneous saccharification and fermentation of cellulosic substrates derived from Canadian Ponderosa Pine. Conclusions The combinatorial strategies of metabolic engineering and adaptive evolution enabled to constructC. glutamicum strains that were able to co-ferment cellobiose and xylose. This work could be useful in development of recombinantC. glutamicum strains for efficient lignocellulosic-biomass conversion to produce value-added chemicals and fuels.